(untitled) (The 40th International Pupils’ Attitudes Towards Technology Conference Proceedings 2023, 2023)
University students have different motives and expectations when it comes to going on exchange and taking university courses in another country. Similarly, different motives and requirements impact course choices. Some exchange students who come to Finland choose to participate in craft courses. Craft as a school subject can be a new and foreign experience for many of them. The aim of this study is to investigate international students’ rationales for taking craft courses during their university studies in Finland. It also focuses on what kinds of expectations they have from a craft course and how they are met. This was a qualitative study. Data was collected through questionnaires at the beginning (n=26) and end (n=15) of a craft course in which both international students and Finnish students had enrolled. Only international students’ answers were reported. Students answered open-ended questions about why they chose the course and their expectations from the course. At the end of the course, they were asked how it met their expectations. Themes for motives and expectations were identified using reflexive thematic analysis. Motives for the students’ choices related to their interests in the craft subject, their development, benefits in future work, new opportunities and practical studio work. Expectations related to, among other things, participants’ learning and development, learning from and helping each other, and learning things that would be useful in future work. The findings suggest that the content of craft courses is important and relevant to learn among students with diverse cultural backgrounds, regardless of whether they have similar subjects in their home countries.